Integrasi smart agriculture technology map dan model objective matrix untuk analisis key performance indicators (KPI) pengelolaan greenhouse - Dani Yudiastono; Nafis Khuriyanti; Mohammad Affan Fajar Falah (AGROINTEK, 2024)
Key Performance Indicators (KPI) for Agriculture is a guide to assessing performance in agriculture using 5 work indicators: efficiency, quality, capacity index, work environment, and maintenance. The purpose of this study is to identify the level of technology application in greenhouses based on the Smart Agriculture Kaizen Level (SAKL) technology mapping, determine a systematic performance appraisal method in greenhouses, and evaluate the operational performance of Greenhouse Pandanaran, Gunung Kidul Regency. The use of technology and utilization of production data is very important to support the level of productivity of an agricultural system. Moreover, in the transition process from traditional agriculture to agriculture based on smart agriculture, actual research is needed to support its performance against Agricultural KPIs. Through this research, the relationship between the level of technology application and agricultural KPIs in greenhouse production will be obtained Initial research was carried out by identifying the level of technology application in several greenhouse samples and then performing a performance assessment based on Agricultural KPIs. In the performance appraisal based on KPI Agriculture conducted in the greenhouse, the productivity value is obtained from the Objective Matrix (OMAX) method. The use of OMAX includes calculating 3 (three) indicators: efficiency, quality, and capacity index. The study results show that the Pandanaran Greenhouse performance assessment uses the OMAX method from May 2021 to November 2022 (19 months). 11 months are equal to or above standard productivity. The highest overall productivity was achieved in November 2022, whereby the cultivation method implemented in November 2022. From this research, it was found that the best results in aquaponic cultivation were obtained by using fish as the main product and vegetables as a side product.